Mathematics for computer science calculus - Mohd Aboobaider, Burhanuddin; Abdul Rahman, Ahmad Fadzli Nizam; Abal Abas, Zuraida; Asmai, Siti Azirah (FTMK, 2008)
This module covers one of the disciplines of mathematics that will be taught in Mathematics for Computer Science students, which is Calculus. Topics for Calculus include functions, derivatives, integrals, definite integrals, exponential, natural logarithm functions and functions of several variables. Student will use this practical module during tutorial session throughout the semester.